Experimental Determination of Dispersion Coefficient in Soil - Anthony Chibuzo Ekeleme; Jonah. C. Agunwamba (Ital Publication, 2018)
Unsaturated soil dispersion experiment was done using three different soil samples which includes sand, clay and silt soil. The objective of the study is to determine experimentally dispersion coefficient in soil. Each sample was gradually introduced into a fabricated iron column, having a length of horizontal column 30cm and vertical part 60.96cm. A solution of silver nitrate was allowed to pass through the vertical column down to the horizontal part. Samples of soil were collected at a constant distance of 10cm and time interval of 5mins for 60mins .The concentration of nitrate was taken at a constant distance of 10cm .This was done three times for each of the soil sample. Thereafter, the dispersion coefficient was calculated, and a regression dispersion model developed as a function of permeability, average diameter of sieve, velocity of flow and time taken to flow. The model was calibrated and verified with experimental results and found to have a high correlation coefficient (r) of 0.943. Data obtained from the experiments were fitted into the two existing models and poor correlation coefficients of -0.529 and -0.524 were obtained respectively.